Water allocation policies for the Dong Nai River Basin in Vietnam: an integrated perspective - Ringler, Claudia; Vu Huy, Nguyen (International Food Policy Research Institute, 2004)
Recent water sector reforms, increased scarcity and vulnerability of existing water resources, combined with declining public funding available for large-scale infrastructure investment in the sector have led to an increased awareness by the Government of Vietnam for the need to analyze water resource allocation and use in an integrated fashion, at the basin scale, and from an economic efficiency perspective. This paper presents the development, application, and results from an integrated economic-hydrologic river basin model for the Dong Nai River Basin in southern Vietnam that attempts to address these issues. The model framework takes into account the sectoral structure of water users (agriculture, industry, hydropower, households, and the environment), the location of water-using regions, and the institutions for water allocation in the basin. Water benefit functions are developed for the major water uses subject to physical, system control, and policy constraints. Based on this modeling framework, policies that can affect water allocation and use at the basin level, including both basin-specific and general macroeconomic policies, are analyzed.